2018
DOI: 10.1021/acs.nanolett.8b00304
|View full text |Cite
|
Sign up to set email alerts
|

Fano Description of Single-Hydrocarbon Fluorescence Excited by a Scanning Tunneling Microscope

Abstract: The detection of fluorescence with submolecular resolution enables the exploration of spatially varying photon yields and vibronic properties at the single-molecule level.By placing individual polycyclic aromatic hydrocarbon molecules into the plasmon cavity formed by the tip of a scanning tunneling microscope and a NaCl-covered Ag (111) surface, molecular light emission spectra are obtained that unravel vibrational progression. In addition, light spectra unveil a signature of the molecule even when the tunnel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 61 publications
7
35
0
Order By: Relevance
“…], by calculating the coupling strength between the picocavity plasmons 19 , i.e., electromagnetic modes confined to an atomic-scale volume at the apex of the plasmonic tip, and the Q x and Q y transition dipole moments of H 2 Pc. As observed previously 15,16,24 this coupling results in an increased (attenuated) emission intensity for the tip localized at the extremities (center) of the molecular dipoles. In our case, the extreme spatial localisation of the field is responsible for the close to atomic-scale spatial resolution in the fluorescence maps.…”
Section: Together With Other Observations This Remote Excitation Indsupporting
confidence: 76%
See 1 more Smart Citation
“…], by calculating the coupling strength between the picocavity plasmons 19 , i.e., electromagnetic modes confined to an atomic-scale volume at the apex of the plasmonic tip, and the Q x and Q y transition dipole moments of H 2 Pc. As observed previously 15,16,24 this coupling results in an increased (attenuated) emission intensity for the tip localized at the extremities (center) of the molecular dipoles. In our case, the extreme spatial localisation of the field is responsible for the close to atomic-scale spatial resolution in the fluorescence maps.…”
Section: Together With Other Observations This Remote Excitation Indsupporting
confidence: 76%
“…4(c)) but with the tip located ≈ 1.2 nm laterally away from the molecule (see STM image in inset). In this configuration, it has been shown that the molecule can still be driven to its excited state through energy transfer between the tunneling electron and the molecular exciton 20,24,31 . In contrast, processes directly activated by tunneling electrons traversing the molecule, such as charging 32 , cannot occur.…”
Section: The Gmentioning
confidence: 99%
“…Finally, in the present work, we describe the excitation mechanism in terms of virtual photon coupling because energy transfer from the tunnel current to the excitons occurs without the participation of an intermediary optical mode such as a localized surface plasmon polariton [62]. In a different context (i.e., STM electroluminescence of single molecules), a comparable excitation mechanism has recently been reported in terms of inelastic electronmolecule scattering [63].…”
Section: Scanning Tunneling Microscope-induced Excitonic Luminescencementioning
confidence: 83%
“…The experimental and theoretical findings presented in this work likewise shed light onto the notion of electronic decoupling, which is generally used to characterize the extent of hybridization of an adsorbate with the hosting substrate. The weak hybridization is often attributed to the submolecular resolution in STM images of adsorbed molecules, [ 206–210 ] the occurrence of electronic states, [ 211–219 ] vibrational quanta, [ 220–224 ] and fluorescence photons [ 225–237 ] with particularly sharp spectroscopic line shapes. In the case of graphene, the results summarized here are able to provide a more precise and quantitative description of the hybridization.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%